2011
DOI: 10.1016/j.nedt.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Service user and carer involvement in student nurse selection: Key stakeholder perspectives

Abstract: SUMMARYThe aim of this study was to evaluate an innovation where service users and carers were involved in the recruitment of child and adult nursing students. Seventy candidates, four service users and carers and six academics who had been involved in the selection process took part in the study. A short questionnaire was administered to the nursing candidates. Two semi structured group interviews were undertaken, one with the service users and carers and another with the academics. Findings reveal that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Academic colleagues and practice partners also regard this enhancement as highly effective, which mirrors the findings of Rhodes and Nyawata (2011) who found that both academics and service users viewed their involvement in the selection of nursing students as positive and a move towards a gold standard in student nurse selection.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
“…Academic colleagues and practice partners also regard this enhancement as highly effective, which mirrors the findings of Rhodes and Nyawata (2011) who found that both academics and service users viewed their involvement in the selection of nursing students as positive and a move towards a gold standard in student nurse selection.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 61%
“…It also allowed them to make a rich and meaningful contribution to all aspects of the programme, encompassing the design of modules, recruiting students, teaching and assessment, reviewing and evaluation of the programme. Mackey and Millar (2012) carried out a study of the involvement of young people and adult SUACs in the classroom with social work students and echoed the recommendations of previous studies (for example, Rhodes and Nyawata, 2011;Speed et al, 2012) in their findings regarding the need to avoid tokenism, and to ensure a sound organisational commitment to providing effective support, enabling structures and processes. Happell et al (2015) chose a telephone interview methodology with nurse academics from 27 Australian universities involved in SUAC input into pre-registration and postgraduate mental health nurse training.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The findings of Ion, Cowan and Lindsay (2010) regarding the need for mutual respect and the valuing of difference are echoed throughout this study, as is the need to adequately prepare and develop SUAC colleagues (Anghel and Ramon, 2009;Mackey and Millar, 2012) if SUAC involvement is to be meaningful. Findings also suggest that academics might usefully spend more time in planning and preparation, utilising SUACs in this process so that inequalities of power dynamics, cited as barriers by previous commentators (Masters et al, 2002;Felton and Stickley, 2004;Baldwin and Sadd, 2006;Rhodes and Nyawata, 2011), are reduced and planning is not entirely staffbased. Perceptions from staff in earlier studies regarding the difficulty in reaching a balance between tokenism and meaningful SUAC involvement (Molyneaux and Irvine, 2004;Taylor et al, 2006) were not supported in the present study, where strong organisational support and positive staff attitudes emerged.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Involvement in the recruitment of students is discussed by Vandrevala (2007), with the involvement of users in the selection of clinical psychology students. Matka (2009) describes the approach to involvement in admissions to social work and clinical psychology, and Rhodes & Nyawata (2010) evaluated involvement in the selection of student nurses. These three papers identified that user involvement had a positive impression on candidates, who felt that users had a right to be involved in recruitment, due to their experience as recipients of healthcare.…”
Section: Uses Of the Conceptmentioning
confidence: 99%